Parents', Teachers' and Principals' Views on Parental Involvement in Secondary Education Schools in Greece - Sophia Anastasiou; Aggeliki Papagianni (MDPI AG, 2020)
The objective of the present study was to investigate parents’, teachers’ and principals’ views on parental involvement (PI) in Secondary Education Schools in Greece. The research was based on a survey among parents (n = 54), teachers (n = 84) and principals (n = 12) in twelve Secondary Education Schools in Magnesia Region in central East Greece. Different views between each group were exhibited on PI in educational issues, decision making or creating links and communication between the school and the local community. Teachers expressed the view that workload and parental attitudes are factors which discourage parental involvement in their school units. Parents felt that teachers’ professionalism, lack of teachers’ training on parental involvement and parents who hesitate talking to teachers were significant barriers for PI in their school units. School principals agreed with parents and teachers on the barriers established due to teachers’ professionalism and parents’ hesitation in talking to teachers as significant factors which discourage PI in their school units. Contrarily to teachers’ views, school principals expressed their willingness to increase PI in teachers’ and school evaluation. School leaders should explore the possibility of organising meetings with teachers and parents to reduce barriers and misconceptions, paving the way for communication between the school unit and parents, increasing the positive outcomes of PI in school management and students’ success.